2
$\begingroup$

For the surface $\sigma(u,v)= (\frac{\cos v}{\cosh u}, \frac{\sin v}{\cosh u}, \tanh u)$, compute the geodesic curvature and the normal curvature of:

(i) a meridian $v$ = constant,

(ii) a parallel $u$ = constant.

Which of these curves are geodesics?

I know that a meridian is a geodesic and its geodesic curvature $\kappa_g = 0$.

From the textbook, the normal curvature $\kappa_n = \gamma''·N$ and the geodesic curvature $\kappa_g = \gamma'' · (N \times \gamma')$, where $N$ is the unit normal of the surface, and $\gamma$ is a unit-speed curve in $\mathbb{R}^3$.

How can I find the $\gamma$ in the formula? Thanks!

$\endgroup$
1
$\begingroup$

By keeping $u$ or $v$ constant in the parametrisation $\sigma$ of the surface and keeping the other parameter "variable", you obtain the parametrisation of the coordinate lines.

For instance, to parametrise a meridian, keeping $v$ constant gives $$ \gamma(t) = \sigma(t, v_0) = \left(\frac{\cos v_0}{\cosh t}, \frac{\sin v_0}{\cosh t}, \tanh t\right). $$

In the same way, if you keep $u$ fixed and let the other parameter of $\sigma$ be the variable of the curve, you get parametrisations of the parallels.

$\endgroup$
1
$\begingroup$

Normal and geodesic curvature of curves on a surface can be computed using the following formulae: \begin{equation} k_n=\frac{q}{s'^2} \\ k_g=\frac{p}{s'^3} \end{equation} where \begin{equation} q=L_{11} u'^2+2 u' v' L_{12}+v'^2 L_{22} \\ p=\left[\Gamma_{11}^2 u'^3+(\Gamma_{22}^2-2 \Gamma_{12}^1) u' v'^2+(u' v''-u'' v')+(2 \Gamma_{12}^2-\Gamma_{11}^1)u'^2v'-\Gamma_{22}^1 v'^3\right] \sqrt{Det(g)} \end{equation} where $\Gamma_{jk}^i$ are the Christoffel symbols of the second kind, $L_{ij}$ the coefficient of the second fundamental form and g the first fundamental form. Independently of the case u=const or v=const, the product $u' v'$ are zero since or v is constant or u is constant. Thus, the above expressions reduce to: \begin{equation} q=L_{11} u'^2+v'^2 L_{22} \\ p=\left[\Gamma_{11}^2 u'^3-\Gamma_{22}^1 v'^3\right] \sqrt{Det(g)} \end{equation} In addition $s'=\sqrt{g_{11}u'^2+2 g_{12} u'v'+g_{22}v'^2}$ reduces to $s'=\sqrt{g_{11}u'^2+g_{22}v'^2}$. We can now consider the two cases.

  1. v=const

In such a case we have \begin{equation} q=L_{11} u'^2 \\ p=\left[\Gamma_{11}^2 u'^3\right] \sqrt{Det(g)}\\ s'=\sqrt{g_{11}u'^2} \end{equation}

  1. u =const

In such a case we have \begin{equation} q=v'^2 L_{22} \\ p=\left[-\Gamma_{22}^1 v'^3\right] \sqrt{Det(g)} s'=\sqrt{g_{22}v'^2} \end{equation} When computing the non zero coefficient of the first fundamental form for $\sigma$, we have $g_{11}=g_{22}=\rm sech^2(u)$, while non zero coefficient of the second fundamental form are $L_{11}=L_{22}=-\rm sech^2(u)$. When replacing these coefficient in the above expression we have 1. v=const \begin{equation} k_n=-1 \\ k_g=0 \end{equation} because $\Gamma_{11}^2=0$. Since the geodesic curvature is zero, the curve is a geodesic.

  1. u=const \begin{equation} k_n=-1 \\ k_g=-\rm sech{(u_0)} \end{equation} where $u_0$ is the constant. The definition of normal and geodesic curvature in your textbook can be written in term of p and q for practical computation.
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.